PROFESSIONAL ZAKAT FOR CIVIL SERVANTS (ASN): Policy Controversies under Aceh Governor Regulations - Muhammad Imam An-Nasa'i; Abdul Manan; Nufiar Nufiar; Rahimah Embong; Muhammad Adli (UIN Sumatera Utara, 2026)
This study explores the ongoing debate surrounding the implementation of professional zakat for Civil Servants (ASN) in Aceh, particularly the automatic 2.5% salary deduction mandated by Aceh Governor Regulation No. 8 of 2022. The controversy extends beyond legal and Islamic jurisprudential considerations, touching on broader questions of social justice, individual agency, and the legitimacy of state intervention in religious obligations. The research seeks to map the contours of this debate by examining legal and fiqh perspectives, public discourse across mass and social media, and its practical implications for ASN. Adopting a descriptive qualitative approach with controversy mapping, the study draws on document analysis, participatory observation, in-depth interviews, and digital narrative analysis. The findings reveal that ASN responses are shaped by varying levels of religious understanding, trust in zakat institutions, and personal financial realities. While some perceive the policy as supportive of religious practice, others experience it as coercive, lacking transparency, and ethically contentious. Keywords: Professional Zakat, Civil Servants (ASN), Controversy